Proposta metodológica de avaliação integrada de riscos na infraestrutura de sistemas hídricos por meio do programa Risco-Fuzzy – estudo de caso: sistema de aporte de água bruta para a região metropolitana de Fortaleza - Codes, Rodrigo Amaral de (2016)
The developed communities, in all their activities, are permanently, and each To a complex set of risks. Risk is, therefore, a concept that Has an increasing importance in contemporary society with an impact on different Aspects thereof. Water systems, in turn, are areas of potential Concept of risk assessment and risk management, taking into account that the objectives In the environment or in economic sustainability, resulting from uncertainties, Extreme events, errors or other events. To ensure system security Several methodologies have been developed with applications to specific cases. Because they are complex processes, based on inaccurate or Approximate, many of the studies have also considered the use of Fuzzy Systems, Which are based on Fuzzy Logic, because they fit well with the type of analysis in question. O This paper initially discusses general aspects of risk assessment and risk management. Related to some water systems, also addressing the theoretical foundations of Preliminary Hazards (APP) and Fuzzy Systems. Its main objective, however, The presentation of a methodological proposal consisting of the formulation of a Risk analysis in which it is possible to subdivide the analyzed water system into several Levels. Therefore, the individual values ​​of the various types of risk can be obtained Involved in the study, the risks of the subsystems in which they are distributed, and The overall risk of the system. It also proposes the construction of a system of fuzzy inference, Where the pertinence functions are suggested for the input language variables Possibility of Occurrence and Severity of Consequences and for the linguistic variable of Output, as well as establishing value scales for them. For the Analysis, the Risk-Fuzzy Program was developed specifically for this purpose. It then evaluates the proposed methodology, as a Case Study, based on data already Which were drawn up at the Water Resources Management Company (COGERH), in the System of Gross Water Supply for the Metropolitan Region of Fortaleza (SAAB / RMF). It also concludes that, for the scenarios considered, the SAAB / RMF, with regard to the frequency and severity of possible risks, it is Both in quantity and water quality. It presents, Finally, new perspectives for studies and research that can complement or Study.